Pioneer adaptation farmers inspire adoption of climate-smart innovations in Bomet County, Kenya - Onyango, Polycarp Otieno; Kiptoo, Emmaculate; Maiyo, Nathan (International Livestock Research Institute, 2025)
In Bomet County, Kenya, the Yebei and Koske families are redefining smallholder farming through climate-smart practices. Using modest farms, they implement innovations like improved fodder, rotational grazing, rainwater harvesting, biogas, and record-keeping to increase milk production, reduce calving intervals, and strengthen food security. Both households actively share knowledge through field days and training sessions, inspiring neighbors and promoting community learning. Their approach emphasizes efficiency, resilience, and women’s participation in farming decisions. By blending tradition with adaptation, these families demonstrate how small, well-managed farms can thrive under climate change, benefiting both households and the wider community.